Vortex Rings - Akhmetov, D. G. (Springer Berlin Heidelberg, 2009)
This book presents a comprehensive coverage of the wide field of vortex rings. The book presents the results of systematic experimental investigations, theoretical foundation, as well as the practical applications of vortex rings, such as the extinction of fires at gushing gas and oil wells. All the basic properties of vortex rings as well as their hydrodynamic structures are presented. Special attention is paid to the formation and motion of turbulent vortex rings.